2007
DOI: 10.1108/14684520710764096
|View full text |Cite
|
Sign up to set email alerts
|

Online reporting by banks: a structural modelling approach

Abstract: PurposeA structural equation model is proposed to explain internet reporting by banks. The model relates three constructs of financial institutions (size, financial performance, and internet visibility) to their final influence on internet information disclosure (e‐transparency).Design/methodology/approachThis paper's proposed model analyses a sample of Spanish financial institutions using publicly available data. The model is tested using partial least squares.FindingsA positive and statistically significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 80 publications
2
25
0
13
Order By: Relevance
“…Therefore, company size is a significant determinant of company value for manufacturing companies listed on the IDX. This result is consistent with previous studies that found size to have a positive and significant impact upon company value (Awwalia, 2014;Chakrabarti et al, 2007;Chen & Ho, 2000;Kumar, 2005;Mickkelson et al, 1997;Ming & Gee, 2008;Serrano-Cinca et al, 2007;Zeitun & Tian, 2007). Investors associate company size with better value.…”
Section: H5: Company Size (Lnmve) Has a Positive And Significant Inflsupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, company size is a significant determinant of company value for manufacturing companies listed on the IDX. This result is consistent with previous studies that found size to have a positive and significant impact upon company value (Awwalia, 2014;Chakrabarti et al, 2007;Chen & Ho, 2000;Kumar, 2005;Mickkelson et al, 1997;Ming & Gee, 2008;Serrano-Cinca et al, 2007;Zeitun & Tian, 2007). Investors associate company size with better value.…”
Section: H5: Company Size (Lnmve) Has a Positive And Significant Inflsupporting
confidence: 82%
“…Company size is manifested by the natural log of total assets and the natural log of the market value of equity. LnAssets is the natural log of total assets (Li et al, 2006;mitton, 2002;Serrano-Cinca et al, 2007) LnMVE is measured as the natural log of market value of equity (Kumar, 2005;Mitton, 2002;Titman & Wessel, 1988) Error…”
Section: Methodsmentioning
confidence: 99%
“…Según Falk y Miller, (Falk & Miller, 1992), estos valores deben ser superiores a 0.1 para poder considerar que el modelo tiene suficiente capacidad predictiva. Así pues, considerando que el R 2 es una medida de la exactitud del modelo (Hair et al, 2014), y que por tanto mide la cantidad de varianza del constructo que es explicada por el modelo (Serrano-Cinca et al 2007) con los valores 0.75, 0.50, 0.25, respectivamente, se describen los niveles sustanciales, moderados o débiles de la exactitud de la predicción (Hair et al, 2014;Henseler et al, 2009), aunque se considera que con valores de 0.2 se obtiene un buen poder explicativo de los constructos (Ajamieh, Benítez, Braojos, & Gelhard, 2016). La estructura del modelo presentado y las relaciones que en él se establecen están en línea con otros estudios similares (p.e Gallardo-Vázquez & Sánchez-Hernández, 2014b;Wang et al, 2015).…”
Section: Análisis Del Modelo Estructuralunclassified
“…Although Cronbach's alpha for three categories (accessibility, timeliness and company information) is below the often-suggested acceptable level of 0.7 (e.g. SerranoCinca, Fuertes-Callén & Gutiérrez-Nieto, 2007;Nunnaly, 1978;Kelton & Yang, 2008), it can still be viewed as acceptable given the alpha of 0.51 as reported by Gul and Leung (2004) and 0.64 reported by Botosan (1997). Gul and Leung (2004) did however admit that the low alpha reported in their results suggested that random measurement error could reduce the power of the empirical tests in their study.…”
Section: Reliabilitymentioning
confidence: 99%